Indonesia Reaps the Benefits of Business Performance SME Manufacturing Industry Technology Revolution - Cheng-Wen Lee; Taufiqquddin Ande (Indonesian Journal of Multidisciplinary Science, 2022)
The purpose of this study is to determine the extent to which SMEs in Indonesia apply lean manufacturing and industrial technology 4.0. The results of this study indicate that Indonesian SMEs partially and simultaneously have a positive impact. Lean manufacturing systems have an important relationship with the three pillars of Industry 4.0. Excluding equipment and methods and product design. Respondents in the study were 25 SME owners, directors, managers, and deputy managers, the statements and interview questions were based on all aspects of lean manufacturing. in this study only 3 indicators out of 9 Industry 4.0 indicators, namely, additive manufacturing, augmented reality, and simulation in Indonesian SMEs. This research uses SPSS software version 20.0 and E-Views version 10.0.